Life cycle analysis of beverage packaging - Maidin, Shajahan; Ismail, Shafinaz; Azman, Azmiza Idayu (Penerbit UTM Press, 2024)
Plastic is the leading food and item packaging material due to its lightweight characteristics. However, there have been alarming concerns over the past years since the large-scale introduction of plastic after the Second World War, and a total of 8.3 billion metric tons have been produced. This research aims to compare the environmental impact of the packaging design of several consumer products using life cycle analysis (LCA). Based on the openLCA open-source software, three beverage packaging types were compared: plastic bottles, glass bottles, and aluminium cans. The life cycle inventory (LCI) must be identified based on case studies, literature reviews and relevant assumptions to obtain the result. Then, each beverage packagings flows, process and product system was also required to be identified to run the openLCA software. The three types of packaging was compared within each CML category in terms of impact. The CML stands for "Centrum voor Milieukunde Leiden". It is a research institute of the Centre for Environmental Studies at Leiden University located in the Netherlands and a procedure used to estimate the measure of environmental impact caused by the product. Based on the CML eleven impact categories, the plastic bottle was ranked as the most impactful towards the environment, followed by glass bottles and aluminium cans as the least impactful. Other than that, it may be due to the quantity of material being used, the effect of the material during processing, and the recyclable ability.